Design and analysis battery packaging for electric vehicle (EV) - Sibra Mallisi, Yussof (2009)
Battery packaging is the packaging where the batteries Lead-acid or Lithium-Ion are kept safe. Battery packaging is installed in car such as electric vehicle, hybrid electric vehicle or the car that needs to convert to the electric vehicle. Batteries selection is made depend on the motor specification that install in the car. The battery packaging are important to make the performance of batteries are stable. The cooling system of battery packaging is used to make the heat flow in battery packaging not exceeding the operating temperature of the batteries. The proposed design is made to reach the design specification of battery packaging. Some of battery packaging is made without cooling system. More criteria needs to consider in order choosing the battery packaging such as cost, weight, available space, compact, maintenances and more. The selection of battery packaging must have all the criteria needed by battery packaging, therefore the analysis are made for selection material and heat transfer from battery packaging to outside of the car. The cooling system is effect most on the performance, weight, cost, and maintenances. For example, the liquid cooling system most effective than air cooling system, but liquid cooling have more deficiency in leakage problem, need more mass to complete the circulate of the cooling system and also higher cost of maintenances. The air cooling system less effective, but the cost is low than liquid, easy maintenance and also less mass. So that, this project is focus on cooling system type air to find most effective cooling system by three proposed design of air cooling system. At the end of this project, a new design of proposed battery packaging has been choose by using Solid Work software. There are some improvements have been made in order to reach the design criteria. As the result of this battery packaging design and analysis, the objective to design battery packaging and select the suitable battery packaging, analysis on the faster type design heat transfer from battery packaging to outside of the car can be achieved.